Regional Development Planning and Policy in the Aspects of Vulnerability and Disaster Resilient Cities: A Review - Rakuasa, Heinrich; Latue, Philia Christi (Sinergi International Journal of Communication Sciences, 2023)
Disaster management in the world has undergone a paradigm change that is from responsive to preventive, from sectoral to multi-sector, from government responsibility solely to joint responsibility, centralization to decentralization and from emergency response to disaster risk reduction. Based on 6 directives of the President of the Republic of Indonesia delivered during the Rakornas PB (Disaster Management) at surabaya, February 2, 2019 one of which is "Regional development planning must be based on aspects of DRR (Disaster Risk Reduction)". Disaster risk-based regional development planning aims to reduce the impact of disaster risk including, threats, vulnerabilities, and capacity. Vulnerability assessment in areas that have the potential to experience disaster events is one of the important factors that must be reviewed in disaster mitigation efforts. Vulnerability assessment with the concept of data from wisdom allows local policymakers to recognize their specific situation in the broader context of a similar situation, providing regional perspectives and important connections between regions. Based on the efforts that have been integrated between the program into city spatial planning, it is hoped that it can increase the resilience of the City in facing disasters and adapt to climate change.